Mathematical Model to Predict the Soil Macronutrients Status under the Influence of Phosphorus and Manure for Continuous Cropping System - Khajanchi, M; Sharma, R; Pancholi, U (International Journal of Computer Sciences and Engineering, 2025)
In the present work we studied, how phosphorus fertilizer and manure affect the soil status of other macronutrients like nitrogen and potassium using mathematical model. By knowing the status of nutrients availability, a producer can manage things and get high crop yield. The model was applied to five fertilizer practices of a two year field experiment entitled “Integrated nutrient management in blackgram”, conducted in Rajasthan College of Agriculture, Udaipur, Rajasthan, India.